Abdomen anatomic characteristics on CT scans as predictive markers for short-term complications following radical resection of colorectal cancer - Zhang, Xiao; Yang, Zhengyang; Meng, Cong; Gao, Jiale; Liu, Yishan; Shi, Bohao; Sun, Liting; Wu, Guocong; Yao, Hongwei; Zhang, Zhongtao (Frontiers in Surgery, 2022)
Background: Prediction and management of postoperative short-term complications in patients with colorectal cancer are very important in postoperative rehabilitation. Through CT scan, we can easily measure some parameters of abdomen anatomic characteristics. The aim of this study was to assess whether there is a relationship between the abdomen anatomic characteristics and postoperative short-term complications. Materials and Methods: we conducted a retrospective study. Eighty patients in each complication group and non-complication group were recruited with propensity score match. Demographics, perioperative laboratory results, surgical information were collected and compared between groups with univariate analysis. Significant elements were brought into subsequently logistic regression analysis and ROC analysis for further identification. Results: Univariate analysis showed that preoperative white blood cells, preoperative neutrophil counts, rectus abdominis thickness (RAT), subcutaneous fat thickness (SFT), abdomen depth (AD) were significantly different between the complication group and non-complication group. Logistic regression analysis demonstrated that higher RAT (p = 0.002), SFT (p < 0.001) and AD (p < 0.001) independently predicted the incidence of short-term postoperative complications. Conclusions: In this study on patients undergoing radical resection of colorectal cancer, abdomen anatomic characteristic including higher RAT, SFT and AD are associated with an increased risk of short-term postoperative complications.